2011
DOI: 10.1007/s11481-011-9326-z
|View full text |Cite
|
Sign up to set email alerts
|

Morphine and gp120 Toxic Interactions in Striatal Neurons are Dependent on HIV-1 Strain

Abstract: A rigorously controlled, cell culture paradigm was used to assess the role of HIV-1 gp120 ± morphine in mediating opioid-HIV interactive toxicity in striatal neurons. Computerized time-lapse microscopy tracked the fate of individual neurons co-cultured with mixed-glia from mouse striata during opioid and gp120 exposure. Subpopulations of neurons and astroglia displayed μ-opioid receptor, CXCR4, and CCR5 immunoreactivity. While gp120 alone was or tended to be neurotoxic irrespective of whether X4-tropic gp120II… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
62
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 47 publications
(64 citation statements)
references
References 125 publications
2
62
0
Order By: Relevance
“…Our studies conclusively show that opiates can directly exacerbate the deleterious effects of HIV-1 on neurons in an infective model in vitro , although past studies have demonstrated that morphine interacts with the HIV-1 proteins Tat [21], [23] and gp120 [24]. The present studies also confirm and extend prior findings of glial involvement in interactions between opiates and HIV proteins, demonstrating that combined morphine and HIV-1 SF162 neurotoxicity can be amplified in the presence of glia.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Our studies conclusively show that opiates can directly exacerbate the deleterious effects of HIV-1 on neurons in an infective model in vitro , although past studies have demonstrated that morphine interacts with the HIV-1 proteins Tat [21], [23] and gp120 [24]. The present studies also confirm and extend prior findings of glial involvement in interactions between opiates and HIV proteins, demonstrating that combined morphine and HIV-1 SF162 neurotoxicity can be amplified in the presence of glia.…”
Section: Discussionsupporting
confidence: 85%
“…Opiate drugs of abuse have been shown to enhance particular damaging effects of HIV-1 proteins in vitro [21][24], [72]. However, the CNS of HIV-1-infected patients is exposed to a great many other cellular and viral factors released from infected and/or activated cells.…”
Section: Discussionmentioning
confidence: 99%
“…This notion is in consistence with previous studies that virus, Tat and gp120 may directly contribute to HAND (Paris et al 2015;Podhaizer et al 2012;Zou et al 2007). Because gp120 glycoproteins can be taken up by brain microvessels and transported across the BBB (Banks et al 2005), it is possible that higher brain P24 antgenemia in HIV-1 JR-FL -infected mice contribute to severer neuron damages as compared with HIV-1 BJZS7 -infected animals.…”
Section: Discussionsupporting
confidence: 81%
“…Because gp120 glycoproteins can be taken up by brain microvessels and transported across the BBB (Banks et al 2005), it is possible that higher brain P24 antgenemia in HIV-1 JR-FL -infected mice contribute to severer neuron damages as compared with HIV-1 BJZS7 -infected animals. However we cannot exclude the possibility that HIV-1 strain-specific differences in Tat and gp120 may also determine the neurotoxicity (Podhaizer et al 2012). To this end, more T/F viruses should be tested in future studies.…”
Section: Discussionmentioning
confidence: 94%
“…57 The activated macrophages and microglia begin to release inflammatory cytokines (for example, TNFa), chemokines and other neurotoxins 54,55 to enhance the neuropathy.…”
Section: Discussionmentioning
confidence: 99%